Banking in India - Panandikar, S. G.; Mithani, D. M. (Bombay : Orient Longman, 1975)
This edition added four new chapters including: the issue of bank nationalization, social control of commercial banks, India after nationalization, social control of commercial banks, Indian banking after nationalization - retrospect and prospect, and a review of the banking commission report.
Includes index.
Bibliography: p. [648]-652.
osc 24/8/17
Loans
Keywords: Banks and Banking; India